Natural aerosol direct and indirect radiative effects. Issue 12 (19th June 2013) - Rap, Alexandru; Scott, Catherine E.; Spracklen, Dominick V.; Bellouin, Nicolas; Forster, Piers M.; Carslaw, Kenneth S.; Schmidt, Anja; Mann, Graham
<x xml:space="preserve">Abstract</x> [1] Natural aerosol plays a significant role in the Earth's system due to its ability to alter the radiative balance of the Earth. Here we use a global aerosol microphysics model together with a radiative transfer model to estimate radiative effects for five natural aerosol sources in the present‐day atmosphere: dimethyl sulfide (DMS), sea‐salt, volcanoes, monoterpenes, and wildfires. We calculate large annual global mean aerosol direct and cloud albedo effects especially for DMS‐derived sulfate (–0.23 Wm–2 and –0.76 Wm–2, respectively), volcanic sulfate (–0.21 Wm–2 and –0.61 Wm–2) and sea‐salt (–0.44 Wm–2 and –0.04 Wm–2). The cloud albedo effect responds nonlinearly to changes in emission source strengths. The natural sources have both markedly different radiative efficiencies and indirect/direct radiative effect ratios. Aerosol sources that contribute a large number of small particles (DMS‐derived and volcanic sulfate) are highly effective at influencing cloud albedo per unit of aerosol mass burden.